(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The development of the digital economy is one of the important strategic tasks for the Republic of Uzbekistan, the process of which serves to increase the global competitiveness of the country. For the rapid development of the digital economy, it is important to create infrastructure by the state, support technological innovation and accelerate digital transformation in the main sectors of the economy. This process will help to form an effective management system in the country, develop a business environment and expand the opportunities of the population to use digital services.